Possibilities of using fly ash after denitrification to various types of building materials. Issue 1 (1st September 2022) - Chromkova, I; Kubatova, D; Bohm, P; Cechmanek, R; Dzurov, M; Kukletova, I; Simbera, T
Abstract : The paper summarises information gained within the verification of high-temperature fly ashes after the denitrification process. There was an examination of characteristics of fly ashes from various heat sources as well as possibilities of using these types of fly ashes to various types of building applications. An effect on final properties of a building material produced in laboratory or experimental conditions was observed. Positive results were achieved within the verification of using fly ash to fly ash-cement mixtures. A quality of prepared suspensions was equal to the practically verified one prepared from a fly ash from a powerplant without SNCR. These mixtures after 28 days achieved compressive strengths 8 MPa. Significant increase of strengths in the course of time was recorded. After 90 days compressive strengths achieved values 13-16 MPa and after 1 year even 17-20 MPa. Flexural strengths after 28 days were around 1.5 MPa. This parameter also showed a tendency to increase in time. Fly ash after denitrification was effective within a preparation of repairing materials based on epoxy resin. For these materials, 50% substitution of natural aggregate with fly ash after denitrification process was proven. Final strength characteristics of the new prepared material outperformed a reference mixture, containing only natural fine-grained aggregate/filler. A using of fly ash as a compound of filler of alkali-activated systems was also tested. Fly ash after SNCR in the amount of 20 to 60% in combination with fine-milled blast furnace slag and sodium water glass was tested. These materials achieved compressive strengths 50–75 MPa and flexural strengths 6–10 MPa.